Country ownership and capacity building: the next buzzwords in health systems strengthening or a truly new approach to development? - Goldberg Jessica; Bryant Malcolm (BMC, 2012)
Abstract Background During the last decade, donor governments and international agencies have increasingly emphasized the importance of building the capacity of indigenous health care organizations as part of strengthening health systems and ensuring sustainability. In 2009, the U.S. Global Health Initiative made country ownership and capacity building keystones of U.S. health development assistance, and yet there is still a lack of consensus on how to define either of these terms, or how to implement "country owned capacity building". Discussion Concepts around capacity building have been well developed in the for-profit business sector, but remain less well defined in the non-profit and social sectors in low and middle-income countries. Historically, capacity building in developing countries has been externally driven, related to project implementation, and often resulted in disempowerment of local organizations rather than local ownership. Despite the expenditure of millions of dollars, there is no consensus on how to conduct capacity building, nor have there been rigorous evaluations of capacity building efforts. To shift to a new paradigm of country owned capacity building, donor assistance needs to be inclusive in the planning process and create true partnerships to conduct organizational assessments, analyze challenges to organizational success, prioritize addressing challenges, and implement appropriate activities to build new capacity in overcoming challenges. Before further investments are made, a solid evidence base should be established concerning what works and what doesn't work to build capacity. Summary Country-owned capacity building is a relatively new concept that requires further theoretical exploration. Documents such as The Paris Declaration on Aid Effectiveness detail the principles of country ownership to which partner and donor countries should commit, but do not identify the specific mechanisms to carry out these principles. More evidence as to how country-owned capacity building plays out in practice is needed to guide future interventions. The Global Health Initiative funding that is currently underway is an opportunity to collect evaluative data and establish a centralized and comprehensive evidence base that could be made available to guide future country-owned capacity building efforts.